ANALYSIS OF THE IMAGE AND OBJECTS RECOGNITION ON THE BASIS OF SKELETON-CONTOUR REPRESENTATION - N. A. Maximov; A. V. Scharonov (Научный вестник МГТУ ГА, 2016)
The information technology of recognition of aircraft type aircraft on images obtained from aerial photography. The developed method is based on the analysis of skeleton-contour characteristics is discussed. The main signs of recognition and the analysis of the sustainability of the procedure of all kinds of noises and distorting factors recognition. The results can be used at creation of program-algorithmic support of special systems of unmanned aerial vehicles (UAV).